THE DEVELOPMENT OF ETHNOMATHEMATICS-BASED STUDENT WORKSHEETS (LKPD) IN MATHEMATICS FOR FOURTH GRADE STUDENTS - Sudiyah Anawati; Seruni; Mia Intan Lestari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
This study aims to determine the quality of Ethnomathematics-based math worksheet learning plans for fourth grade students of Madrasah Ibtidaiyah on the material circumference and area of flat shapes. The type of research used is research and development with the ADDIE model. The data source for this research was obtained from the validation results of three validators and the results of student questionnaires. The data collection technique uses a validation questionnaire. The results showed that this study used five steps, namely the Analysis, Design, Development, Implementation and Evaluation stages. The results of the validity of the Ethnomathematics-based mathematics LKPD were 77.46 in the good category. While the results of the student questionnaire assessment were 84.15 in the good category. The quality of Ethnomatematics-based math worksheets for fourth graders of Madrasah Ibtidaiyah can be seen from two aspects, namely the results of expert validation and the results of student questionnaires, both of which obtained good.